2023
DOI: 10.1186/s12884-023-05728-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between oxytocin and combination of tranexamic acid and ethamsylate in reducing intra-operative bleeding during emergency and elective cesarean section after 38 weeks of normal pregnancy

Almandouh H. Bosilah,
Elsayed Eldesouky,
Moatazza Mahdy Alghazaly
et al.

Abstract: Objective Cesarean Section (CS) is associated with an increased risk of hemorrhage. Many drugs are used to decrease this risk. We aim to compare the combination of ethamsylate and tranexamic acid, oxytocin, and placebo in women undergoing CS. Methods We conducted a double-blinded, randomized, placebo-controlled trial between October and December 2020 in four university hospitals in Egypt. The study included all pregnant women in labor without any c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…In this study of intraoperative blood loss, the TXAEth group demonstrated significantly lower intraoperative blood loss than the oxytocin group. This result is consistent in all included studies [19][20][21]. It is affirmed that TXA and Eth are associated with a significant reduction in intraoperative blood loss compared to a placebo [22].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In this study of intraoperative blood loss, the TXAEth group demonstrated significantly lower intraoperative blood loss than the oxytocin group. This result is consistent in all included studies [19][20][21]. It is affirmed that TXA and Eth are associated with a significant reduction in intraoperative blood loss compared to a placebo [22].…”
Section: Discussionsupporting
confidence: 83%
“…Although a statistically significant distinction in postoperative hematocrit levels was observed between the two cohorts, there was no analogous difference in hemoglobin levels. Nevertheless, the decline in both Hb (-0.5 ± 0.2 and -1.77 ± 1.16 vs -0.9 ± 0.2 and -1.78 ± 1.12) and Hct (-1.5 ± 1.4 and -5.84 ± 3.91 vs -2.57 ± 1.6 and -5.84 ± 3.91) was less pronounced in the TXAEth group compared to the oxytocin group (Table 2) [19,21]. This implies that TXAEth might exhibit greater efficacy in mitigating blood loss during surgical procedures.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations